PECULIARITIES OF FORMING A FORENSIC CHARACTERISTIC IN CASE OF CAUSING NEGLIGENT SERIOUS OR MODERATE BODILY HARM (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the theoretical and applied issues of criminalistics with regard to determining the specific features of the conceptual framework and the essence of the forensic characterisation of negligent grievous or moderate bodily harm as a scientific category. The article examines the positions of scientists on the issues of defining the conceptual framework for forensic characterisation of certain types of crimes and develops the author's own definition of causing negligent grievous or moderate bodily harm. The article examines the correlation between the criminalistic characteristics of this type of criminal offence and the peculiarities of legal qualification of this type of crime in comparison with intentional infliction of grievous or moderate bodily harm. Based on the results of this research, the article provides suggestions and recommendations for improving the provisions of Article 128 of the Criminal Code of Ukraine and for highlighting the features of the forensic characteristics of negligent grievous or moderate bodily harm in theoretical and law enforcement terms.
Keywords: concept; essence; forensic characteristic; crime; features; criminal offence; improvement; theory; law enforcement; bodily injury; featuresdiscussion